Phase II study of intensified rituximab induction and maintenance for low grade B cell lymphoma. Issue 12 (2nd December 2017) - Nagai, Hirokazu; Shimomura, Takeshi; Takeuchi, Makoto; Hanada, Shuichi; Komeno, Takuya; Sunami, Kazutaka; Hidaka, Michihiro; Yano, Takahiro; Kitano, Kiyoshi; Yoshida, Isao; Inoue, Nobumasa; Saito, Akiko; et al.
Abstract: Rituximab has markedly improved the outcomes of B cell lymphoma, and its maintenance has been shown to be beneficial in low grade B cell lymphoma (LGBCL). We conducted a multicenter, phase II trial of intensive rituximab induction and maintenance therapy for LGBCL to optimize the rituximab monotherapy. Patients with newly diagnosed or rituximab naïve relapsed LGBCL received 8 weekly rituximab as induction, then continued maintenance therapy with rituximab for 4 weeks at 6-month intervals. The primary endpoint was the overall response rate (ORR). Forty-five patients were enrolled from 2005 to 2009 and 36 were eligible. The ORR was 83.3% (30/36) with a complete response rate of 72.2% (26/36). The 3-year progression-free survival (PFS) was 76.7% with a median follow-up of 43.0 months. Five grade three toxicities were observed (no grade 4). Our findings suggest that this regimen demonstrates high activity with durable PFS and minimal toxicity in LGBCL patients.